2014
DOI: 10.1159/000356199
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Profile of CADASIL Patients with R544C Notch3 Mutation

Abstract: Background: Cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an inherited microangiopathy caused by mutations in the Notch3 gene. In the present study, we aimed to analyze cognitive and neuroimaging profiles of CADASIL patients with R544C mutation. Methods: Fifty-eight consecutive patients with R544C mutation and 26 normal controls were investigated. The patients were divided into two groups depending on the presence (CADASIL with dementia: CADASIL-D) or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
4
0
2
Order By: Relevance
“…The phenotype mentioned in the miscellaneous periodical of CADASIL presenting with parkinsonism are distributed throughout the various mutation sites [9][10][11]. What calls for special attention concerns that there are few clinical case reports or the other researchers referred parkinsonism as the primary clinical performances of CADASIL with R544C mutation [2,[12][13][14][15]. We conclude previous studies in Table 1.…”
Section: Discussionsupporting
confidence: 62%
“…The phenotype mentioned in the miscellaneous periodical of CADASIL presenting with parkinsonism are distributed throughout the various mutation sites [9][10][11]. What calls for special attention concerns that there are few clinical case reports or the other researchers referred parkinsonism as the primary clinical performances of CADASIL with R544C mutation [2,[12][13][14][15]. We conclude previous studies in Table 1.…”
Section: Discussionsupporting
confidence: 62%
“…Through meta‐analysis, a negative association was found between MMSE and white matter lesions volumes (r = –.26, 95% CI [–.43; –.09], n = 217), number of lacunes (r = –.40, 95% CI [–.69; –.12], n = 136) and number of microbleeds (r = –.22, 95% CI [‐.38; –.06], n = 188) in cSVD patients (in, respectively, 5, 3, and 2 studies, Table 3). 17,19,51,103–105 No significant pooled correlation was found between MMSE and white matter hyperintensity diffusion tensor imaging indexes (2 studies, data not shown) 106,107 . One single not meta‐analyzable study found a high negative correlation between MoCA performance and volumes of white matter lesions (r = –.47, n = 56) 103 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐five studies compared cSVD and healthy controls performances at targeted tests (16 sporadic cSVD and 9 CADASIL). 18 , 19 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 Among these studies, 20 compared performances at MMSE; 9 at MoCA; 13 at TMT‐A; 14 at TMT‐B; 8 at Stroop test; 5 at Boston Naming Test; 8 and 4 at phonemic and semantic fluency, respectively (Table 1 and Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few researchers have investigated constructional apraxia (CA)—that is, the inability to produce a complex figure by putting its parts in the correct spatial relationship (Kleist, 1934), occurring in visuoconstructional tests—in individuals with CADASIL (Zuluaga-Castaño et al, 2018). CA has been reported in individuals who are affected by cognitive deterioration (Da Silva et al, 2011; Song et al, 2014), but such impairments can also occur independently from general cognitive impairment. Ragno et al (2012) observed CA on visuoconstructional tests in asymptomatic individuals with CADASIL with mild cognitive decline.…”
mentioning
confidence: 99%